2016
DOI: 10.1002/jmor.20539
|View full text |Cite
|
Sign up to set email alerts
|

Morphological analysis of the hagfish heart. II. The venous pole and the pericardium

Abstract: The morphological characteristics of the venous pole and pericardium of the heart were examined in three hagfish species, Myxine glutinosa, Eptatretus stoutii, and Eptatretus cirrhatus. In these species, the atrioventricular (AV) canal is long, funnel-shaped and contains small amounts of myocardium. The AV valve is formed by two pocket-like leaflets that lack a papillary system. The atrial wall is formed by interconnected muscle trabeculae and a well-defined collagenous system. The sinus venosus (SV) shows a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 50 publications
0
9
2
Order By: Relevance
“…Icardo et al (2016) were unable to observe specialized nodal tissue in the sinus wall or at the sinoatrial junction. Yet, electrocardiogram recordings in E. cirrhatus (Davie et al, 1987) showed a depolarization specific to only the central region of the sinus venosus, something not seen, however, in M. glutinosa (Arlock, 1975;Satchell, 1991).…”
Section: Discussionmentioning
confidence: 90%
“…Icardo et al (2016) were unable to observe specialized nodal tissue in the sinus wall or at the sinoatrial junction. Yet, electrocardiogram recordings in E. cirrhatus (Davie et al, 1987) showed a depolarization specific to only the central region of the sinus venosus, something not seen, however, in M. glutinosa (Arlock, 1975;Satchell, 1991).…”
Section: Discussionmentioning
confidence: 90%
“…In squid, vascular endothelial growth factor (VEGF) and FGF receptors have been found in embryonic vessels, pointing to conserved signaling pathways; however, more studies are necessary to establish the gene regulatory networks in molluscan cardiogenesis. The circulation system in hagfish, the most ancestral of extant vertebrates, is special as it includes several accessory pumps to the branchial heart, which is equivalent to the heart in other vertebrates . These hearts exhibit limited looping and absent OFT elements.…”
Section: Cardiac Precursorsmentioning
confidence: 99%
“…As the sinus venosus is myocardialized in many species, it can be considered a true cardiac chamber. It will remain recognizable as a separate structure in hagfish connected to the left side of the common atrium, but in birds and most mammals (except monotremes) it will become incorporated in the dorsal atrial wall (Figure ). In lungfish, a separate pulmonary channel traverses the main atrial compartment and delivers oxygenated blood directly to the ventricle .…”
Section: The Atrial Segmentmentioning
confidence: 99%
“…Small amounts of myocardium can be noted inside the canal, which incorporates a two‐leafed AV valve without any defining papillary muscles (Icardo et al. ).…”
Section: Early Vertebrate Heartmentioning
confidence: 99%
“…Underneath the atrium is a single ventricle, which is attached via an elongated atrioventricular (AV) canal. Small amounts of myocardium can be noted inside the canal, which incorporates a two-leafed AV valve without any defining papillary muscles (Icardo et al 2016).…”
Section: Jawless Fish (Infraphylum Agnatha)mentioning
confidence: 99%